Resistome Analysis of Global Livestock and Soil Microbiomes - Lawther, Katie; Santos, Fernanda Godoy; Oyama, Linda Boniface; Rubino, Francesco; Morrison, Steven; Creevey, Chris J.; McGrath, John W.; Huws, Sharon Ann (Frontiers in Microbiology, 2022)
Antimicrobial resistance (AMR) is a serious threat to public health globally; it is estimated that AMR bacteria caused 1.27 million deaths in 2019, and this is set to rise to 10 million deaths annually. Agricultural and soil environments act as antimicrobial resistance gene (ARG) reservoirs, operating as a link between different ecosystems and enabling the mixing and dissemination of resistance genes. Due to the close interactions between humans and agricultural environments, these AMR gene reservoirs are a major risk to both human and animal health. In this study, we aimed to identify the resistance gene reservoirs present in four microbiomes: poultry, ruminant, swine gastrointestinal (GI) tracts coupled with those from soil. This large study brings together every poultry, swine, ruminant, and soil shotgun metagenomic sequence available on the NCBI sequence read archive for the first time. We use the ResFinder database to identify acquired antimicrobial resistance genes in over 5,800 metagenomes. ARGs were diverse and widespread within the metagenomes, with 235, 101, 167, and 182 different resistance genes identified in the poultry, ruminant, swine, and soil microbiomes, respectively. The tetracycline resistance genes were the most widespread in the livestock GI microbiomes, including tet(W)_1, tet(Q)_1, tet(O)_1, and tet(44)_1. The tet(W)_1 resistance gene was found in 99% of livestock GI tract microbiomes, while tet(Q)_1 was identified in 93%, tet(O)_1 in 82%, and finally tet(44)_1 in 69%. Metatranscriptomic analysis confirmed these genes were “real” and expressed in one or more of the livestock GI tract microbiomes, with tet(40)_1 and tet(O)_1 expressed in all three livestock microbiomes. In soil, the most abundant ARG was the oleandomycin resistance gene, ole(B)_1. A total of 55 resistance genes were shared by the four microbiomes, with 11 ARGs actively expressed in two or more microbiomes. By using all available metagenomes we were able to mine a large number of samples and describe resistomes in 37 countries. This study provides a global insight into the diverse and abundant antimicrobial resistance gene reservoirs present in both livestock and soil microbiomes.